Gut Microbiota Variation in Aging Dogs with Osteoarthritis - Fatemeh Balouei; Christina de Rivera; Andrea Paradis; Bruno Stefanon; Stephanie Kelly; Noelle McCarthy; Paolo Mongillo (Animals)
Gut microbiota composition plays a crucial role in host health and may be influenced by age and disease conditions. This study investigates the gut microbiota diversity of 175 dogs across three age groups (Junior (20–46 months, 43 dogs), Adult (47–92 months, 58 dogs), and Senior (93–168 months, 74 dogs), and examined the impact of osteoarthritis on microbial composition. Alpha diversity analysis using the Shannon and Chao1 indices were significant (p < 0.05) in Senior dogs Beta diversity analysis based on Bray–Curtis dissimilarity indices demonstrated substantial overlap in gut microbiota composition across age groups, with no significant clustering observed (p > 0.05). A second analysis compared the microbiota of 69 healthy dogs and 81 dogs affected by osteoarthritis (OA) in the three classes of age. No significant differences were shown for alpha diversity and beta diversity between healthy and OA dogs. This indicates that aging and osteoarthritis do not induce significant shifts in microbial beta diversity, although high inter-individual variability was noted. Linear Discriminant Analysis (LDA) Effect Size (LEfSe) analysis identified distinct bacterial taxa associated with different age groups. Linear Discriminant Analysis (LDA) Effect Size (LEfSe) analysis identified distinct bacterial taxa associated with different age groups. Junior dogs exhibited enrichment in Blautia, Erysipelotrichaceae, and Clostridium, while Adult dogs were characterized by higher abundances of Prevotella, Streptococcus, and Ruminococcaceae. Senior dogs had increased representation of Prevotella and Ruminococcus. In OA dogs, Peptococcus, Peptostreptococcus, Clostridiaceae, and Coprobacillus were significantly enriched in comparison to healthy dogs, suggesting potential microbiota shifts associated with osteoarthritis. Overall, these findings indicate that gut microbiota diversity varies across different life stages, specific bacterial taxa were differentially enriched in relation to age and OA. This study enhances our understanding of gut microbiota dynamics in dogs and provides insights into potential age- and disease-related microbial signatures.